1991
DOI: 10.1016/0014-5793(91)81416-6
|View full text |Cite
|
Sign up to set email alerts
|

Binding of inositol phosphates to arrestin

Abstract: Arrcstin binds to phosphorylavzd rhodopsin in its light-activated form (melarhodopsin II), blocking thcrcby its interaction with the G-protein, mmsducin. In this study, WC show thal highly phosphorylatcd forms of inositol compete against the arrcslin-rhodopsin inlcraction. Competition curves and direct binding assays with free arrcslin consislcntly yield affinities in the micromolar range; for example, inositol 1.3.4.5-telrakisphospharc (InP,) and inosilol hcxakisphosphalc (InP, bind to arrcstin with dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 23 publications
4
69
0
Order By: Relevance
“…When the deutero-acetylation experiments were repeated in the presence of heparin, small decreases (<lo%) in acetylation were observed at 6 lysines with the greatest protection of highly polycationic peptide TV232-242 and peptide TV292-302 (data not shown), regions that were weakly protected during interaction with P-Rho*. These data are consistent with an overlap of binding regions for heparin and P-Rho* and for the reported competition between P-Rho* and heparin for the binding to arrestin (Palczewski et al, 1991b.…”
Section: Arrestin/p-rho* Interactionssupporting
confidence: 76%
“…When the deutero-acetylation experiments were repeated in the presence of heparin, small decreases (<lo%) in acetylation were observed at 6 lysines with the greatest protection of highly polycationic peptide TV232-242 and peptide TV292-302 (data not shown), regions that were weakly protected during interaction with P-Rho*. These data are consistent with an overlap of binding regions for heparin and P-Rho* and for the reported competition between P-Rho* and heparin for the binding to arrestin (Palczewski et al, 1991b.…”
Section: Arrestin/p-rho* Interactionssupporting
confidence: 76%
“…These two interactions activate arrestin, allowing its transition into a high affinity receptor-binding state (2). Several lines of evidence suggest that a major conformational rearrangement of the arrestin molecule is a part of this transition (2)(3)(4)(5). First, arrestin binding to the receptor has a very high Arrhenius activation energy (3).…”
mentioning
confidence: 99%
“…As mentioned before, the concave surface of the N-domain contains a cationic region that has been implicated in the recognition of the phosphorylated state of rhodopsin (21,31). Thus, in the case of the 162myc163-R*P interaction, the anti-Myc antibody may exert its inhibitory effect by shielding this cationic region.…”
Section: Fig 2 Binding Of Wild-type and Myc-tagged Arrestin Mutantsmentioning
confidence: 96%
“…6, lanes 11 and 12). Previous studies have shown that heparin and other negatively charged ligands such as light-activated phosphorylated rhodopsin or the synthetic 7PP are able to bind arrestin and induce a conformational change in the molecule (20,26,31,38). Although it has been determined that the conformational changes induced by these ligands may not be identical, an enhanced susceptibility to proteolysis of arrestin C terminus is a common effect (38).…”
Section: Fig 2 Binding Of Wild-type and Myc-tagged Arrestin Mutantsmentioning
confidence: 99%
See 1 more Smart Citation